2007
DOI: 10.1364/ol.32.002671
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of femtosecond Yb-doped fiber amplifiers to tens of microjoule pulse energy via nonlinear chirped pulse amplification

Abstract: We demonstrate that the compensation of self-phase modulation by third-order dispersion can be exploited in the design of fiber amplifiers with tens of microjoules pulse energy. At the highest energies, the amplified pulse accumulates nonlinear phase shift as large as 17 pi. Gain-narrowing occurs in the final amplifier stage, but shorter pulses are still generated with larger nonlinear phase shifts. A large-mode-area Yb-doped photonic crystal fiber amplifier generates diffraction-limited 30 microJ pulses, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 0 publications
0
46
0
Order By: Relevance
“…Considerable work has been done during the recent past either to scale up the pulse energy [13,20,21] or the average power [22][23][24] from YDF amplifier by employing novel pulse shaping techniques and by using novel fibre geometry. Shah et al [20] demonstrated more than 100 μJ of pulse energy with 650 fs pulse duration.…”
Section: Fibre Amplifier and Its Characterizationmentioning
confidence: 99%
“…Considerable work has been done during the recent past either to scale up the pulse energy [13,20,21] or the average power [22][23][24] from YDF amplifier by employing novel pulse shaping techniques and by using novel fibre geometry. Shah et al [20] demonstrated more than 100 μJ of pulse energy with 650 fs pulse duration.…”
Section: Fibre Amplifier and Its Characterizationmentioning
confidence: 99%
“…16 So far, a challenge still exists in the art of ultrafast fiber laser design to generate high-energy sub-100-fs pulses. A straightforward solution is to combine nonlinear spectral broadening 17,18 and divided-pulse amplification 12 by seeding an upchirped pulse into a negativedispersion fiber amplifier.…”
mentioning
confidence: 99%
“…Recently, several modifications have been introduced -pulse shaping [3] or misaligned stretcher and compressor configuration [4] -to push pulse energy limits even further. Most of the setups reported so far utilize two or more amplification stages [5][6][7] to obtain tens of J energy levels with a reduced (<1 MHz) repetition rate. Other works explore the limits of the highest possible pulse energy or average power [3,8] at the expense of significant complication of the amplifier set-ups.…”
mentioning
confidence: 99%